Teaching to the curriculum or teaching to the test - Roseline Sama; Jeneth Yemisi Adegbuyi; Mercy Ifunanya Ani (Journal of Social, Humanity, and Education, 2021)
Purpose: This research aimed to investigate teaching practices that dominates the West African Senior Secondary Certificate Examination class to ascertain discrepancies between the prescribed and implemented curriculum. Research methodology: The study adopted ex-post facto research design of a survey type. 1719 students and 53 mathematics teachers participated in the study. Four instruments were used for data collection: Mathematics Content Completion Inventory, Teaching Depth Rating Scale(r=0.96), Classroom Observation Checklist(r=0.95) and Mathematics Learning Task(r=0.95). Data were analyzed using descriptive statistical model in SPSS version 20. Results: Results indicated that Full implementation of the prescribed curriculum ranged between 46.2% to 86.5% for 54 topics, but only three out of them were indepthly taught. Teaching activities revolved around examination preparation, with the highest percentage of 48.55 among nine different categories. Limitation: This study was limited to only one state in Nigeria, one subject and one type of high-stakes examination. It can be replicated on different school subjects to provide greater generalizability. Contribution: Results will help stakeholders strategise on reforms that will promote in-depth teaching and optimal implementation of the prescribed mathematics curriculum. Keywords: Curriculum, High-Stakes examination, Mathematics, Teaching depth